2023
DOI: 10.3389/fpubh.2023.1233020
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality in a prospective cohort of people who were homeless during the COVID-19 pandemic

Sandrine Loubiere,
Ikrame Hafrad,
Elisabetta Monfardini
et al.

Abstract: IntroductionCertain living conditions, such as homelessness, increase health risks in epidemic situations. We conducted a prospective observational cohort study to investigate the impact of the COVID-19 pandemic on morbidity and mortality in adult people who were homeless.MethodsThe study population comprised around 40% of the entire population experiencing homelessness in Marseille. They were enrolled at 48 different locations during the first pandemic wave (June to August 2020) and were followed up 3 and 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A total of 102 articles were therefore full-text-reviewed; of them, 66 were removed from the analyses as they were not consistent with the research topic, while 3 further reports were removed for not fulfilling the inclusion criteria, and 2 reports were removed for including cases otherwise described in other studies [19][20][21]96,97]. The final sample included a total of 31 studies (0.62% of the initial sample); of them, 17 were prevalence studies [4][5][6]17,18,42,[98][99][100][101][102][103][104][105][106][107][108], 12 studies reported on the incidence of respiratory pathogens [19][20][21]44,[109][110][111][112][113][114][115][116] and the remaining 2 studies reported on the outcome of respiratory infections in HP [117,118]. As two incidence studies also included outcome data, a total of four outcome studies were ultimately retrieved [19,112].…”
Section: Descriptive Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 102 articles were therefore full-text-reviewed; of them, 66 were removed from the analyses as they were not consistent with the research topic, while 3 further reports were removed for not fulfilling the inclusion criteria, and 2 reports were removed for including cases otherwise described in other studies [19][20][21]96,97]. The final sample included a total of 31 studies (0.62% of the initial sample); of them, 17 were prevalence studies [4][5][6]17,18,42,[98][99][100][101][102][103][104][105][106][107][108], 12 studies reported on the incidence of respiratory pathogens [19][20][21]44,[109][110][111][112][113][114][115][116] and the remaining 2 studies reported on the outcome of respiratory infections in HP [117,118]. As two incidence studies also included outcome data, a total of four outcome studies were ultimately retrieved [19,112].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…A total of four outcome studies were retrieved. Two of them included data collected from the Seattle area [19,117], while the remaining papers detailed cases from Toronto [112] and Marseille [118] (one study each). Two reports included data on both HP and the general population, for a total of 32,091 HP and 1,576,936 non-HP [117,118].…”
Section: Characteristics Of Outcome Studiesmentioning
confidence: 99%
See 3 more Smart Citations